(untitled) (Research, Society and Development, 2022)
The skin is the largest organ of the human body and its state closely reflects the state of health in which the complex human organism finds itself. In addition, the skin is exposed daily to environmental damage that can lead to premature aging, hyperpigmentation, dehydration and even skin diseases such as cancer. Along with the increase in life expectancy, alternatives have been increasingly sought that allow the maintenance of skin health, in order to protect it against harmful environmental damage or symptoms of cellular degeneration, with consequent hyperpigmentation, photoaging and even skin cancer. In view of this, the sciences of nutrition together with aesthetic medicine are present together, since the skin is shown as a sensitive indicator of nutritional deficiencies. Therefore, in order to maintain healthy skin, it is necessary to nourish it with important nutrients for the body through a diversified and balanced diet. Many compounds act effectively in preventing skin aging, with evidence using in vitro, animal, and human models. The objective of this study, therefore, was to review the literature to demonstrate how the bioactive substances present in the diet influence the aging process and their importance in the physical aspects of the skin such as hydration, elasticity, color, firmness and wrinkles.